Determinants of Basic Immunization Completeness among Infants: An Analysis of Maternal Socio-Demographics, Knowledge, Attitudes, and Practices - Lelin Julita Putri; Greiny Arisani; Nurul Fauziah (SIGn Journal of Public Health, 2025)
The administration of basic immunization constitutes a fundamental public health intervention in mitigating infant morbidity and mortality rates associated with Vaccine-Preventable Diseases (VPDs). Despite its pivotal role, the achievement of Universal Child Immunization (UCI) in Palangka Raya City remains fluctuating and consistently falls below national targets. This study aims to comprehensively describe the determinants influencing the status of basic immunization completeness among infants at the Independent Midwifery Practice (IMP) “W” in Palangka Raya City. A descriptive quantitative research design with an observational approach was employed. The sample consisted of 53 respondents drawn from the population using the Slovin formula, with primary data collection conducted through a calibrated questionnaire exhibiting a high reliability coefficient (Cronbach’s Alpha 0.86). Data were processed using univariate statistical analysis to describe frequency distributions and proportions. The results revealed that 62.26% of infants had received complete immunization, while the remaining 37.74% were incomplete. Significant findings indicated that respondents with tertiary education, income exceeding the Regional Minimum Wage (UMP), and those with “Good” knowledge, attitude, and practice categories achieved an absolute completeness rate of 100.00%. Conversely, adolescent mothers (< 20 years) and those with primary education showed a 100.00% incompleteness rate. Geographical accessibility within a radius of < 1 km recorded higher completeness (73.68%) compared to a radius of > 2 km (55.88%), while the Dayak ethnicity demonstrated the highest completeness rate (83.33%). The study concludes that economic factors, education levels, physical accessibility, and maternal knowledge and attitudes are decisive determinants in achieving immunization status. Policy implications are directed toward strengthening personalized education and active home-visit service strategies to eliminate spatial and sociocultural barriers at the primary healthcare level.